(untitled) (Training and Practice : Journal of Educational Sciences, 2010)
This study presents the differences and similarities of three different pedagogical professions. The first part of the study discusses the reasons which led to the creation and motivated the development of these separate professions. The first reason is that schools and educators had to face – and found it difficult – to manage the social problems that occurred in families due to the economic and social changes in the 1990s. This led to the creation of two new professions: the social educator and the social worker. The other reason is that people with special needs require special education and training which could be provided by training teachers specialized in teaching children with special needs and, focusing on a more specific area, by training conductors for teaching various age groups of children with motor disorders. At the end of this study we compare the special education sociological aspects of these three professions, which share readiness to help and empathy as their most common properties.